2019
DOI: 10.5194/isprs-archives-xlii-2-w11-469-2019
|View full text |Cite
|
Sign up to set email alerts
|

A Workflow for Geometric Colour Photography of Painted Surfaces

Abstract: <p><strong>Abstract.</strong> Colour fidelity is vital when documenting painted surfaces. The 2.5D nature of many painted surfaces makes orthophotos and digital surface models (DSMs) common products of the documentation process. This paper presents a workflow to combine photographic and photogrammetric methods to produce aligned colour and depth (orthophotos and DSMs). First, two photogrammetric software (Agisoft Photoscan and Capturing Reality Reality Capture) were tested to determine if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In the Tomb of Nefertari, color charts and gray cards were used successfully to color correct the images (Figure 5). Maintaining color accuracy during photogrammetric imaging and processing has been investigated on a small canvas painting in a lab by CIMS in Dhanda et al 2019. In this research, Agisoft Metashape was found to process images without manipulating the color values up to 16-bits, whereas RealityCapture altered color values past 8-bits.…”
Section: Color Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…In the Tomb of Nefertari, color charts and gray cards were used successfully to color correct the images (Figure 5). Maintaining color accuracy during photogrammetric imaging and processing has been investigated on a small canvas painting in a lab by CIMS in Dhanda et al 2019. In this research, Agisoft Metashape was found to process images without manipulating the color values up to 16-bits, whereas RealityCapture altered color values past 8-bits.…”
Section: Color Accuracymentioning
confidence: 99%
“…This indicates that some photogrammetric software can affect the color accuracy at high bit depths. Additionally, Dhanda et al 2019 recommended two separate capture workflows to achieve both geometric accuracy and color fidelity with glossy painted surfaces. A geometric capture was carried out at a closer distance with a 50mm lens, followed by a color capture with a 300mm lens placed outside of the range of specular reflection.…”
Section: Color Accuracymentioning
confidence: 99%
“…Thence the correct color extraction to properly visualize the artwork on the screen (usually an RGB-based device) is an operation requiring a high degree of options making the results frequently highly biased when compared to the original. More in general, the correct color acquisition and reproduction problem is usually underestimated (Gaiani et al, 2021) with a very low number of studies focused on this topic (Dhanda et al, 2019). The evaluation of the incorrect visualization, often due to color management exploiting the common rendered sRGB color space that leads to non-consistent saturated colors such as cadmium yellow and cobalt blue, among the grayish colors and related issues, is completely missed.…”
Section: Introductionmentioning
confidence: 99%